Allelopathic effect of extracts of Salicornia neei Lag. In the germination of lettuce seeds (Lactuca sativa L.) - Ferreira, Camila Cristina de França; Fernandes, Josimar Gurgel; Campos-Takaki, Galba Maria; Andrade, Rosileide Fontenele da Silva (Seven Editora, 2023)
Salicornia neei is a halophyte plant that has a high interest in food, pharmaceuticals, and health maintenance. In this work, the objective was to evaluate the allelopathic effect of extracts prepared with the root, stem, and leaves of Salicornia neei applied to smooth lettuce (Lactuca sativa L.) seeds. For this, the extracts were prepared using 1g (root, stem, and leaf) macerated and solubilized in water. Then, the smooth lettuce seeds were soaked in the extracts for 30 and 60 minutes. The influence of the extracts on root growth (CR), germination percentage (PG) and germination index (GI) were evaluated. The results showed that the number of lettuce seeds germinated (after soaking for 30 min and 60 min) in all extracts of S. neei (root, stem, and leaf) was higher than the number of germinated seeds in the control treatment. In addition, the maximum germination percentage (PG) was obtained after treatment with seeds soaked in the extracts of S.neei leaf (soaking for 30min) and extract of S.neei root (soaking for 30min), both with PG of 130%. On the other hand, the maximum germination index (GI%) occurred after soaking treatment (for 60min) with S.neei leaf extract.In addition, the extract with the greatest biostimulant potential in root growth was the extract of Salicornia neei leaves (soaked for 60min). Therefore, the investigations carried out in this study show that the seed of smooth lettuce (Lactuca sativa var. capitata) soaked in leaf and root extract for 30 min were the ones that most promoted germination in smooth lettuce (Lactuca sativa var. capitate). DOI:https://doi.org/10.56238/Connexpemultidisdevolpfut-170